17β-Estradiol upregulates ecto-5′-nucleotidase (CD73) in hippocampal synaptosomes of female rats through action mediated by estrogen receptor-α and -β. (2nd June 2016) - Mitrović, N.; Zarić, M.; Drakulić, D.; Martinović, J.; Stanojlović, M.; Sévigny, J.; Horvat, A.; Nedeljković, N.; Grković, I.
Highlights: eN activity and protein level fluctuates across the estrus cycle in the hippocampal synaptosomes. E2 upregulated synaptic eN activity and protein abundance. E2 action is mediated by estrogen receptor-α and -β. E2 had to enter into the intracellular compartment to activate ER(s). ERα induced upregulation of eN protein level and activity, while ERβ increased only eN activity. Abstract: 17β-Estradiol (E2) crucially affects several processes in the hippocampus of both sexes. E2 acts upon estradiol receptors ERα and ERβ, influencing target gene expression and/or modulates intracellular signaling cascades. Another potent modulator of hippocampal function is nucleoside adenosine, the final product of ectonucleotidase cascade, enzymes which hydrolyze extracellular ATP to adenosine. The last and rate-limiting step of the hydrolysis is catalyzed by membrane-bound ecto-5′-nucleotidase (eN). Previous findings obtained on adenosine metabolism in brain suggest that eN may be modulated by ovarian steroids. Therefore, the present study reports that the activity and protein abundance of membrane-bound eN fluctuates across the estrus cycle in the hippocampal synaptosomes of female rats. Further, we analyzed the role of E2 and its intracellular receptors on the expression of eN in ovariectomized females. We found that E2 upregulated eN activity and protein abundance in the hippocampal synaptosomes. Application of nonspecific ER antagonist, ICI 182, 780 and selective ERα and ERβ agonists, PPT and DPN, respectively, demonstrated the involvement of both receptor subtypes in observed actions. Selective ERα receptor agonist, PPT, induced upregulation of both the protein level and activity of eN, while application of selective ERβ receptor agonist, DPN, increased only the activity of eN. In both cases, E2 entered into the intracellular compartment and activated ER(s), which was demonstrated by membrane impermeable E2–BSA conjugate. Together these results imply that E2-induced effects on connectivity and functional properties of the hippocampal synapses may be in part mediated through observed effect on eN.